PERAN PENYULUH PERTANIAN TERHADAP PENINGKATAN KOMPETENSI PETANI KAKAO DI KEC. WOTU KAB. LUWU TIMUR - Khabib Bukhari; Sapar; Anggra Alfian (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2026)
Improving farmers' competence is the process of developing farmers' abilities, knowledge, skills, and attitudes to be better able to manage their farming business effectively, productively, and sustainably. The special purpose of this study is to find out the role of agricultural extension workers in improving the competence of cocoa farmers in Wohu District.This study uses a quantitative approach with a survey method. The number of samples of 100 cocoa farmer respondents was determined purposively. Data collection was carried out through a questionnaire using the Likert scale and analyzed using the Structural Equation Modeling (SEM) approach using the SmartPLS application. The research variables consisted of the characteristics of farmers, the role of extension workers and the competence of farmers were measured through four main indicators. The results showed that the characteristics of farmers did not have a significant effect on the competence of farmers, with a T Statistics value of 1.001 < T Table of 1.984 and a P Value of 0.317 (> 0.05). On the other hand, the role of extension workers has a positive and significant effect on farmers' competence, with a T Statistics value of 16,604 > 1,984 and a P Value of 0.000 (< 0.05). The R-Square value of 0.605 indicates that the two independent variables are simultaneously able to explain 60.5% of the variation in farmer competence, while the rest is influenced by other factors outside the research model.